Randomized Trial of the Effect of Four Second-Generation Antipsychotics and One First-Generation Antipsychotic on Cigarette Smoking, Alcohol, and Drug Use in Chronic Schizophrenia. Issue 7 (July 2015) - Mohamed, Somaia; Rosenheck, Robert A.; Lin, Haiqun; Swartz, Marvin; McEvoy, Joseph; Stroup, Scott
Abstract : Abstract: No large-scale randomized trial has compared the effect of different second-generation antipsychotic drugs and any first-generation drug on alcohol, drug and nicotine use in patients with schizophrenia. The Clinical Antipsychotic Trial of Intervention Effectiveness study randomly assigned 1432 patients formally diagnosed with schizophrenia to four second-generation antipsychotic drugs (olanzapine, risperidone quetiapine, and ziprasidone) and one first-generation antipsychotic (perphenazine) and followed them for up to 18 months. Secondary outcome data documented cigarettes smoked in the past week and alcohol and drug use severity ratings. At baseline, 61% of patients smoked, 35% used alcohol, and 23% used illicit drugs. Although there were significant effects of time showing reduction in substance use over the 18 months (all p < 0.0001), this study found no evidence that any antipsychotic was robustly superior to any other in a secondary analysis of data on substance use outcomes from a large 18-month randomized schizophrenia trial.